Effect of inherent minerals on sewage sludge pyrolysis: Product characteristics, kinetics and thermodynamics. (October 2018) - Tang, Siqi; Zheng, Chunmiao; Zhang, Zuotai
Highlights: Sewage sludge pyrolysis influenced by internal minerals was investigated systematically. Volatile products produced during sludge pyrolysis were characterized using TG-FTIR-GC/MS. Thermodynamic equilibrium simulation for sewage sludge pyrolysis was performed. Inherent minerals increased the total Gibbs free energy of formation for sludge pyrolysis system. Abstract: Inherent minerals in sludge influence sludge pyrolysis behaviors and the final products. In this study, the effects of inherent minerals on sewage sludge pyrolysis were systematically investigated by studying the pyrolysis behaviors of raw sewage sludge (RS) and HCl-washed sludge (WS), and in combination with thermodynamic equilibrium simulations for the hypothetical mineral-free sludge (AS) assumed. The pyrolysis of RS and WS was performed with a novel online thermogravimetric analyzer equipped with an infrared spectrometer and a gas chromatograph coupled with a mass spectrometer (TG-IR-GC/MS). It was found that inherent minerals influenced both the release of volatile products as a function of pyrolysis temperature, and the development of the physicochemical properties of the derived char. In the temperature range of 300–500 °C, hydrocarbons with more than 4 carbon atoms as well as aromatic compounds showed an increased release during WS pyrolysis, with respect to RS, while hydrocarbons with less than 3 carbon atoms such as CH4 and C3 H6 exhibited a decreased release. In addition, the inherent minerals enhanced the release of HCN and NH3, both leading to increased NO2 release, and the release of H2 S and COS was also promoted while the release of CH3 SH, SO2 and CS2 was mitigated. Kinetic analysis confirmed that a catalytic effect induced by the inherent minerals decreased the activation energy at 300–500 °C. Thermodynamic simulations suggested that inherent minerals influenced sludge pyrolysis and the derived products formation by increasing the total Gibbs energy of the sludge pyrolysis system. Therefore, considerations of sludge inherent minerals should be taken into account during pyrolysis for the purpose of value-added commodity production and pollutant mitigation.